The politics of the South - Rampton, David (David L.); Welikala, Asanga; Asia Foundation (Colombo : The Asia Foundation, 2005)
Study funded by various intergovernmental and international agencies.
"Six-part series, volume no. 3."--Cover.
Keywords: Nationalism -- Sri Lanka; Sri Lanka -- Politics and government -- 1978-